Sustentabilidade do extrativismo kaingang de lianas em Porto Alegre/RS - Gravato, Isabel Cristina Ferreira (Universidade do Vale do Rio dos Sinos, 2012)
The vines (lianas) are exploited by traditional communities that require increased use of these products as an alternative for reconciling biodiversity conservation and exploitation of natural resources. The supply chain includes the activities of these plants from the extraction in the forest to end use in the form of handicraft. There is a wealth and abundance of lianas in the region of Porto Alegre, with great diversity of biological attributes. Thus, this study aims to analyze performance and economic aspects of the production chain that involves the manufacture and sale of handicrafts made from lianas and examine the structure and dynamics of three species of lianas used by Kaingangs in Porto Alegre. To characterize the collection strategy, identification and use of vines, field trips were conducted with families Kaingang following the methodology of participant observation, to assess the trade craft identificas 13 families were selling the main selling point of the city of Porto Alegre / RS, the monitoring of sales occurred from September 2008 to August 2009, to check the availability of lianas Kaingang exploited by the community survey was conducted in four remaining peri-urban and over 20 months was conducted in controlled extraction a remnant peri-urban with a history of more than 15 years without extraction of lianas. From the description of the collection was found that lianas Kaingang community focuses its activity on the extraction of a few species of lianas, the average consumption per household is 860.7 m / month, average income is R $ 266.50 / Family; was found that there was no significant difference in the diameter and length of the three species of the control area, in relation to the seasons.
Keywords: Áreas urbanas; Comunidades tradicionais; Conservação; Ecologia humana; Etnobotânica; Urban areas; Traditional communities; Conservation; Human ecology; Ethnobotany; ACCNPQ::Ciências Biológicas::Biologia Geral